Metachronous second primary lung cancer surgically treated five years or more after the initial surgery - KOEZUKA, SATOSHI (Mol Clin Oncol, 2015)
Surgical treatment for metachronous second primary lung cancer following curative resection of primary lung cancer may be challenging. Standard surgical strategies for metachronous second primary lung cancer have not yet been established. The purpose of this study was to evaluate the outcomes of patients who underwent surgical resection for metachronous second primary lung cancer. A total of 12 patients surgically treated for metachronous second primary lung cancer ≥5 years after the initial surgery were retrospectively analyzed. The overall 5-year survival after the second surgery was 56.5%. There was no operative mortality. Patients with T1aN0M0 metachronous second primary lung cancer experienced a significantly higher 5-year overall survival rate compared with other patients (100 vs. 26.7%, respectively; P=0.0336). Among patients who underwent sublobar resection, all 3 patients with T1aN0M0 disease remained alive at the last follow-up, while 4 of the 5 patients (80%) with non-T1aN0M0 disease had developed recurrence. Surgery for metachronous second primary lung cancer may be safely performed. Early-stage metachronous second primary lung cancer was associated with a good prognosis, even among patients who underwent sublobar resection. Early detection of metachronous second primary lung cancer with close long-term follow-up following initial surgery may improve surgical outcomes.